2007
DOI: 10.1080/00071660701671336
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and the immune system

Abstract: 1. Infectious diseases reduce productivity and diminish animal welfare. 2. Appropriate nutrition may aid in minimising the incidence of diseases by enhancing immunity. 3. An understanding of the pressures imposed by evolution that underlie poultry nutrition as well as those which underlie immunity provides focus to the field of nutritional immunology. Additional understanding is provided by knowing the specific cellular mechanisms by which diet affects immunity, and how these mechanisms pertain to specific nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
184
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(212 citation statements)
references
References 101 publications
10
184
0
12
Order By: Relevance
“…Nestes casos a resposta do organismo é a produção aumentada de células e proteínas, como as proteínas de fase aguda sintetizadas pelo fígado (Klasing 2007) e consequente piora no desempenho zootécnico. Este aumento na produção de células como resposta imunológica resulta em redistribuição e maior gasto de nutrientes como lisina.…”
Section: Discussionunclassified
“…Nestes casos a resposta do organismo é a produção aumentada de células e proteínas, como as proteínas de fase aguda sintetizadas pelo fígado (Klasing 2007) e consequente piora no desempenho zootécnico. Este aumento na produção de células como resposta imunológica resulta em redistribuição e maior gasto de nutrientes como lisina.…”
Section: Discussionunclassified
“…First, immune function is affected by host nutrition, which may greatly affect the outcome of infection (Lazzaro and Little, 2009;Schmid-Hempel, 2011). Host nutrition influences both constitutive and inducible immune function, with consequences for morbidity and mortality (Cunningham-Rundles et al, 2005;Klasing, 2007) (Adams and Hewison, 2008;Amar et al, 2007;Calder, 2006;Cohen et al, 2008;Kelley and Bendich, 1996;Klasing, 2007;Kolb, 1997;Kristan, 2007;Samartin and Chandra, 2000;Sorci and Faivre, 2009). Second, nutrition-based interactions are one of the major sources of microbial benefits to animals (Bäckhed et al, 2005;Douglas, 2010;Hooper et al, 2002;Kau et al, 2011;Topping and Clifton, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that estimates for protein and energy requirements for immune processes in animals can be empirically derived (Lochmiller and Deerenberg, 2000;Houdijk et al, 2001;Klasing, 2007). The model of Romanyukha et al (2006) illustrates that empirical estimation of resource requirements for specific immune processes is feasible and can lead to valuable model predictions: after deriving estimates of energy requirements for eight different immune processes relevant in pneumonia infections, their mathematical model could predict whether pneumonia infections will lead to acute or chronic conditions based on energy costs alone.…”
Section: Category 2: Models That Consider the Impact Of Infection On mentioning
confidence: 99%